Biodiversity Sampling Using a Global Acoustic Approach: Contrasting Sites with Microendemics in New Caledonia - Gasc, Amandine (Public Library of Science, 2013)
New Caledonia is a Pacific island with a unique biodiversity showing an extreme microendemism. Many species distributions observed on this island are extremely restricted, localized to mountains or rivers making biodiversity evaluation and conservation a difficult task. A rapid biodiversity assessment method based on acoustics was recently proposed. This method could help to document the unique spatial structure observed in New Caledonia. Here, this method was applied in an attempt to reveal differences among three mountain sites (Mandjélia, Koghis and Aoupinié) with similar ecological features and species richness level, but with high beta diversity according to different microendemic assemblages. In each site, several local acoustic communities were sampled with audio recorders. An automatic acoustic sampling was run on these three sites for a period of 82 successive days. Acoustic properties of animal communities were analysed without any species identification. A frequency spectral complexity index (NP) was used as an estimate of the level of acoustic activity and a frequency spectral dissimilarity index (D(f)) assessed acoustic differences between pairs of recordings. As expected, the index NP did not reveal significant differences in the acoustic activity level between the three sites. However, the acoustic variability estimated by the index D(f), could first be explained by changes in the acoustic communities along the 24-hour cycle and second by acoustic dissimilarities between the three sites. The results support the hypothesis that global acoustic analyses can detect acoustic differences between sites with similar species richness and similar ecological context, but with different species assemblages. This study also demonstrates that global acoustic methods applied at broad spatial and temporal scales could help to assess local biodiversity in the challenging context of microendemism. The method could be deployed over large areas, and could help to compare different sites and determine conservation priorities.